2019
DOI: 10.3847/1538-4357/ab158b
|View full text |Cite
|
Sign up to set email alerts
|

Bondi–Hoyle–Lyttleton Accretion onto Star Clusters

Abstract: An isolated star moving supersonically through a uniform gas accretes material from its gravitationally-induced wake. The rate of accretion is set by the accretion radius of the star and is well-described by classical Bondi-Hoyle-Lyttleton theory. Stars, however, are not born in isolation. They form in clusters where they accrete material that is influenced by all the stars in the cluster. We perform three-dimensional hydrodynamic simulations of clusters of individual accretors embedded in a uniformdensity win… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 58 publications
1
28
1
Order By: Relevance
“…A recent study by Kaaz et al (2019) has shown that the BH accretion rate will depend on the characteristic accretion radius of the cluster 𝑅 acc and the mean separation between stars 𝑅 ⊥ , where 𝑅 ⊥ = 𝑅 cl 𝑁 −1/3 . The average accretion rate of an individual star is given as…”
Section: Gas Accretionmentioning
confidence: 99%
“…A recent study by Kaaz et al (2019) has shown that the BH accretion rate will depend on the characteristic accretion radius of the cluster 𝑅 acc and the mean separation between stars 𝑅 ⊥ , where 𝑅 ⊥ = 𝑅 cl 𝑁 −1/3 . The average accretion rate of an individual star is given as…”
Section: Gas Accretionmentioning
confidence: 99%
“…Sufficiently compact PBH systems could begin accreting coherently which will lead to an enhanced accretion rate when compared to the case where the PBHs are treated as independent accretors. In particular, once their accretion radii start to overlap significantly, a system consisting of N PBHs might start to accrete as a coherent whole, leading to an enhancement by a factor of N compared to the situation with N independent accretors [37,38]. The investigation of this coherent boost factor is another task for this paper.…”
Section: Introductionmentioning
confidence: 99%
“…It's worth taking a moment to contextualize our wind tunnel framework in the landscape of other accretion flows. Our setup is similar to other local simulations of accretion flows, which have proven effective tools for understanding both single and binary BH accretion in a variety of environments, including the ISM (Antoni et al 2019;Kaaz et al 2019, 2020, Schrøder et al 2021 and common envelope evolution (MacLeod & Ramirez-Ruiz 2015a,b;MacLeod et al 2017;Murguia-Berthier et al 2017;De et al 2020;Everson et al 2020). This family of accretion flows essentially considers permutations of Bondi-Hoyle-Lyttleton accretion (for a review, see Edgar 2004) characterized by the gas properties of the surrounding medium.…”
Section: Defining Properties Of the Accretion Flowmentioning
confidence: 96%